من الهندسة النحوية الثنائية الأبعاد إلى الهندسة النحوية الثلاثية الأبعاد أنموذج فرضية هندسة التوازي في نظرية الدلالة التصورية: Linguistic transformation from two-dimensional grammatical engineering to three-dimensional grammatical engineering Parallel geometry hypothesis model in conceptual semantics theory - Ghazioui, Mohamed (SIBAWAYH Arabic Language and Education, 2020)
There is no doubt that the remarkable development in linguistic theories - semantic, syntactic, sound, or purely or other - and their penetration of several cognitive sciences is inevitably due to their benefit from what many sciences such as psychology, neurology, informatics and other cognitive sciences have had, and that has been credited with making transformations. In the structures of linguistic theories, hypotheses, and methods of dealing with linguistic knowledge, and its acquisition are able to address other non-linguistic human knowledge. Let us give an example for these transformations. We wanted to follow in this article one of the fundamental assumptions in the theory of conceptual semantic, which is the hypothesis of parallelism engineering; And that is by identifying what it is, its scientific value, and the alternatives it provides compared with the traditional hypothesis of syntactic grammar, which belongs to the transformative obstetric theory of its American linguist pioneer Noam Chomsky. And the criticisms raised by the linguists. Parallel concrete engineering embodies that transformation from two-dimensional grammatical engineering, or what is referred to as traditional engineering, to three-dimensional engineering based on the fact that semantic, syntax, and phonology are independent components of language, and suggests a different way of operating these components and their interaction, which made its openness possible To study human knowledge with its various variations, rather than to study linguistic knowledge.